CUSTOMER BRAND LOYALTY MODEL FOR SOCIAL MEDIA MARKETING - Wikrama Wardana; R. Dewi Pertiwi; Anthon Tondo; Anwar Sulaiman; Merry Fithriani; Gunawan Gunawan; Lenny Menara Sari Saragih (Sosiohumaniora, 2023)
Identifying the relationship between user engagement, social media marketing, and word-of-mouth referrals to Gojek, an online transportation platform, was the objective of a study conducted in Indonesia. Using a quantitative causal method, researchers gauged the influence of factors like social media marketing and user engagement on customer loyalty. An exclusive group of 300 Instagram followers of Gojek, who had followed and liked their brand page for a minimum of six months, were handpicked for the research. Brand loyalty was identified as the most significant outcome produced through the use of structural equation modeling (SEM). The analysis highlighted a positive and significant effect from the exogenous variables on the endogenous variables. Social media marketing was the key factor contributing to this impact.